Molecular evidence for the hybrid origin of Rosa lichiangensis (Rosaceae) - Zhu, Zhangming; Gao, Xinfen (Phytotaxa, 2015)
Natural hybridization was assumed to play a significant role in the diversification of Rosa. Rosa lichiangensis was suspected to be of hybrid origin based on its intermediate morphological characters between R. soulieana and R. multiflora var. cathayensis. In this study, four chloroplast regions (ndhC-trnV, ndhF-rpl32, ndhJ-trnF, and psbJ-petA) and a single copy nuclear marker (GAPDH) were used to test the hybrid origin of R. lichiangensis. The results from molecular data supported the hybrid origin of R. lichiangensis and further identified R. soulieana as its maternal progenitor and R. multiflora var. cathayensis as the paternal progenitor.